Recognition of hypochondriasis in a clinic for sexually transmitted disease. - Frost, D P (1985)
A descriptive study of 100 consecutive patients referred for psychiatric assessment from a clinic for sexually transmitted disease (STD) is reported. Thirty six patients presented with physical symptoms for which no organic cause could be found. Various physical and psychological features of the overall presentation of this "somatic" group were identified. These are discussed in terms of diagnostic categories, aetiological mechanisms, and theories of illness behaviour. The importance of directly observable aspects of the patients' consultation behaviour is stressed over and above deep psychological constructs. The diagnosis of hypochondriasis is seen as essentially a medical one, which entails the doctor making a set of judgements that require a broad clinical perspective.